Network changes in patients with phobic postural vertigo. Issue 6 (18th April 2020) - Huber, Judita; Flanagin, Virginia L.; Popp, Pauline; zu Eulenburg, Peter; Dieterich, Marianne
Abstract: Introduction: Functional dizziness comprises a class of dizziness disorders, including phobic postural vertigo (PPV), that cause vestibular symptoms in the absence of a structural organic origin. For this reason, functional brain mechanisms have been implicated in these disorders. Methods: Here, functional network organization was investigated in 17 PPV patients and 18 healthy controls (HCs) during functional magnetic resonance imaging with a visual motion stimulus, data initially collected and described by Popp et al. (2018). Graph theoretical measures (degree centrality [DC], clustering coefficient [CC], and eccentricity) of 160 nodes within six functional networks were compared between HC and PPV patients during visual motion and static visual patterns. Results: Graph theoretical measures analyzed during the static condition revealed significantly different DC in the default‐mode, sensorimotor, and cerebellar networks. Furthermore, significantly different group differences in network organization changes between static visual and visual motion stimulation were observed. In PPV, DC and CC showed a significantly stronger increase in the sensorimotor network during visual stimulation, whereas cerebellar network showed a significantly stronger decrease in DC. Conclusion: These results suggest that the altered visual motion processing seen in PPV patients may arise from a modified state of sensory and cerebellar network connectivity. Abstract : Individuals with phobic postural vertigo (PPV) display vestibular symptoms in the absence of a structural or organic origin. For this reason, functional brain mechanisms have been implicated in these disorders. Here, functional network organisation was investigated in PPV patients during functional magnetic resonance imaging with a visual motion stimulus. Notable network organisation changes were found in the sensorimotor and the cerebellar networks.